Buckling of slender composite concrete‐filled steel columns - Goode, C. Douglas; Kuranovas, Artiomas; Kvedaras, Audronis Kazimieras (Journal of Civil Engineering and Management, 2010)
The paper presents the analysis of the experimental data of 1817 on concrete‐filled steel tubes – CFSTs. These results are compared with the predicted results of the load‐bearing capacity of calculations of slender elements according to the methods suggested by Eurocode 4. The following types of tested CFSTs were analysed: circular and rectangular hollow section stub and long columns fully filled with concrete, which were with or without applied moments at the ends of specimen. During the results obtained in the result of the tests on the load bearing capacity for circular concrete‐filled steel tubular columns correspond with the calculated values based on methods presented by Eurocode 4. The experimental values of load bearing capacity for members of concrete‐filled rectangular hollow sections agree very well with the theoretical values where the concrete cylinder strength is below 75 N/mm2. The analysis demonstrated that preloading of concrete‐filled hollow section members does not influence the load bearing capacity. This paper also presents the examination of stress state distribution for concrete‐filled hollow section members, influence of concrete preloading and of longitudinal stress strain curves. First Published Online: 24 Jun 2011